EFEKTIVITAS PENYULUHAN DENGAN MEDIA PUZZLE TERHADAP PENGETAHUAN CARA MENYIKAT GIGI PADA SISWA SD NEGERI 067242 KECAMATAN MEDAN SUNGGAL - Herlinawati Daulay; Ety Sofia Ramadhan; Adriana Hamsar (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Brushing teeth is an action to remove dirt or debris attached to the surface of your teeth, especially after eating breakfast and at night before going to bed, thereby reducing dental health problems. Counseling using puzzle media is conveying information using a game of picture pieces arranged to better understand the information conveyed. This type of research was research with a quasi experiment that research design one-group pretest-postest of counseling using puzzle media on the knowledge of how to brush teeth among students at SD Negeri 067242 Medan Sunggal sub district. The population in this study was 248 students, with samples taken using a purposive sampling technique, 40 students were taken, and data collection was carried out through questionnaires and puzzle media about how to brush your teeth. The research results showed that knowledge before counseling was carried out, students who were in the good knowledge criteria were 2 students (5%) while those with moderate knowledge were 30 students (75%) and those with poor knowledge were 8 students (20%). After counseling, 37 students (92.5%) had good knowledge, 3 students (7.5%) had moderate knowledge, and none had poor knowledge. This research concludes that the level of knowledge of students at SD Negeri 067242 Medan Sunggal sub district is generally a good criterion after counseling using puzzle media. It is hoped that students can maintain healthy teeth and mouth by brushing their teeth every day.